Variations in Central Adiposity, Cardiovascular Fitness, and Objectively Measured Physical Activity According to Weight Status in Children (9–11 Years) - Söğüt, Mustafa; Clemente, Filipe Manuel; Clark, Cain C. T.; Nikolaidis, Pantelis Theodoros; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2019)
The purpose of this study was twofold; first to compare the central adiposity, cardiovascular fitness (CF), and physical activity in children with different weight status, and second, to determine the associations between moderate to vigorous physical activity (MVPA) and measures of adiposity (CA and BMI) and CF. A sample of 244 children (boys= 120, girls=124), 9.7-10.8 years of age (10.3 ± 0.3 years), were measured for stature, body mass, waist circumferences, and twenty-meter Multi-Stage Fitness Test. Physical activity were recorded with ankle mounted accelerometer. BMI groups were used to classify children as underweight (UW), normal weight (NW), and overweight (OW). The prevalence of being overweight was 21.7 and 25% in boys and girls, respectively. Only 5.3% of the participants were found to accumulate recommended amount (≥ 60 min/day) of MVPA. Boys were significantly outperformed girls in terms of CF. Moreover, they were significantly more engaged in moderate and vigorous physical activities than girls. Regardless of gender, results indicated that OW children had significantly higher values in all anthropometric parameters and lower level of CF than their UW and NW counterparts. In girls, OW children were found to accrue less time engaging in MVPA than the children in UW and NW groups. In boys, OW children were found to accrue less time engaging in vigorous activities than UW and NW children. Results also showed that there were no significant differences between UW and NW girls and boys in respect to CF. Besides, UW girls were found to accrue more time engaging in MVPA than NW girls. MVPA was found to be significantly and negatively correlated with BMI and waist circumference, and significantly and positively correlated with CF in both boys and girls. These discrepancies and associations highlight the considerable influences of MVPA on weight status and CF in children.